Estratégias de leitura para o poema: propostas de atividades para o Ensino Fundamental II - Silva, Luiz Danilo Rodrigues da (2021)
Annually large-scale external surveys and evaluations such as Censo Escolar, Ideb and SPAECE indicate, each year, a low index of reading proficiency in public school students and this makes the work of the Portuguese language teacher challenging. It was based on this context that this research, of an interventional nature, was conceived in Mestrado Profissional em Letras - UFC. The target audience of this intervention proposal is the students from the 8th year of junior school. As a general objective, we aim to analyze the importance that the use of reading strategies has on the teaching of Portuguese, especially on students with few experience of literary reading. For this, we selected texts of the poetic genre, as it is a still little explored genre in the classroom (perhaps due to its discursive and polysemic complexity) and, at times, it is a pretext for a purely grammatical analysis in textbooks. The main theoretical basis was anchored in the conceptions of teaching and types of reading according to Geraldi (1985), Silva (2009), Antunes (2009) and Travaglia (2009). Regarding the literary and textual conception of the poetic genre, we highlighted Aristotle (1997), Bakhtin (1997), Soares (2007) and Marcuschi (2010). Regarding the formation of the literary reader and the use of poetry in the classroom, we highlighted Candido (1985), Freire (1997), Cosson (2012) and Pinheiro (2018). Finally, we presented the definitions and examples of reading strategies in Solé (1998), Girotto and Souza (2010), Kleiman (2016) and Koch and Elias (2017). The chosen methodology was action research according to Thiollent (2008) and Bloom's taxonomy revised in Anderson (2001) and Leite Jr (2019). At the end of this work, a proposal for reading workshops with lesson plans and activities was presented acoording to BNCC (2017), which offers the teacher the opportunity to work with some strategies, including connection, prediction and inferring . Despite the limitations of the research due to the pandemic context in the period 2020-2021, the positive balance prevailed in relation to the studies developed and the didactic material offered to students and teachers.